Analisis Rancang Ulang Proses Bisnis Menggunakan Pendekatan Lean Six Sigma (Studi Kasus : PT Bihels Mitra Mandiri) - Ariza Azahra Syuviana (Fakultas Ilmu Komputer, 2024)
This thesis presents research on the topic of Business Process Management (BPM) with the main focus being to analyze business process redesign using the Lean Six Sigma (LSS) approach. The purpose of redesigning business processes using Lea Six Sigma is to identify errors or errors made during the business process, minimize errors and make improvements to business processes so that business processes can be better. The application of Lean Six Sigma in this research uses 5 DMAIC phases, namely Define, Measure, Analysis, Improve and Control. The Define implementation stage is explained using the SIPOC Diagram to see the flow of business processes that occur and identify the 7 Weste. The Measure phase in this research uses FMEA to carry out measurements. The Analysis Phase uses one of the Root Cause Analysis methods, namely 5-Why Analysis. The Improve phase uses Kaizen 5W+1H to find solutions to problems. The final stage is an action plan to control business processes. Business process improvements use new business process modeling described through BPMN which can later be simulated to see that ongoing business processes can be optimized properly so that business process performance can increase.
Entry oleh Arif 2026 Maret 16
Keywords: Lean Six Sigma; BPMN; BPM; DMAIC